Comprehensive Metabolic Phenotyping Refines Cardiovascular Risk in Young Adults. Issue 22 (1st December 2020) - Murthy, Venkatesh L.; Reis, Jared P.; Pico, Alexander R.; Kitchen, Robert; Lima, Joao A.C.; Lloyd-Jones, Donald; Allen, Norrina B.; Carnethon, Mercedes; Lewis, Gregory D.; Nayor, Matthew; Vasan, Ramachandran S.; Freedman, Jane E.; et al.
Abstract : Background: Whereas cardiovascular disease (CVD) metrics define risk in individuals >40 years of age, the earliest lesions of CVD appear well before this age. Despite the role of metabolism in CVD antecedents, studies in younger, biracial populations to define precise metabolic risk phenotypes are lacking. Methods: We studied 2330 White and Black young adults (mean age, 32 years; 45% Black) in the CARDIA study (Coronary Artery Risk Development in Young Adults) to identify metabolite profiles associated with an adverse CVD phenome (myocardial structure/function, fitness, vascular calcification), mechanisms, and outcomes over 2 decades. Statistical learning methods (elastic nets/principal components analysis) and Cox regression generated parsimonious, metabolite-based risk scores validated in >1800 individuals in the Framingham Heart Study. Results: In the CARDIA study, metabolite profiles quantified in early adulthood were associated with subclinical CVD development over 20 years, specifying known and novel pathways of CVD (eg, transcriptional regulation, brain-derived neurotrophic factor, nitric oxide, renin–angiotensin). We found 2 multiparametric, metabolite-based scores linked independently to vascular and myocardial health, with metabolites included in each score specifying microbial metabolism, hepatic steatosis, oxidative stress, nitric oxide modulation, and collagen metabolism. The metabolite-based vascular scores were lower in men, and myocardial scores were lower in Black participants. Over a nearly 25-year median follow-up in CARDIA, the metabolite-based vascular score (hazard ratio, 0.68 per SD [95% CI, 0.50–0.92]; P =0.01) and myocardial score (hazard ratio, 0.60 per SD [95% CI, 0.45–0.80]; P =0.0005) in the third and fourth decades of life were associated with clinical CVD with a synergistic association with outcome ( P interaction =0.009). We replicated these findings in 1898 individuals in the Framingham Heart Study over 2 decades, with a similar association with outcome (including interaction), reclassification, and discrimination. In the Framingham Heart Study, the metabolite scores exhibited an age interaction ( P =0.0004 for a combined myocardial–vascular score with incident CVD), such that young adults with poorer metabolite-based health scores had highest hazard of future CVD. Conclusions: Metabolic signatures of myocardial and vascular health in young adulthood specify known/novel pathways of metabolic dysfunction relevant to CVD, associated with outcome in 2 independent cohorts. Efforts to include precision measures of metabolic health in risk stratification to interrupt CVD at its earliest stage are warranted. Abstract : Supplemental Digital Content is available in the text.